Influence of Rice Husk Ash on Self-Compacting Concrete to Avoid the Presence of Honeycombs in Columns - Marcos Jesus, Boza Rabanal (2024)
In structural columns, honeycombs are very common in small and big works. This problem is caused by poor consolidation of the concrete that increases the probability of honeycombs (voids left in concrete according ACI). These imply costs incurred and affect the work schedule. An exhaustive search is carried out regarding methods in the scientific literature and materials with respect to their availability in the market related to the problem. In this way, it was found that the design of a self-compacting concrete using the ACI 237R-07 with the use of a supplementary cementitious material aims to be a solution to this problem. Rice husk ashes contain silicon oxide and aluminates. These elements improve or increase the strength of the concrete, offer workability and fluidity properties. It was found that with a 5% replacement, 735 mm and 730 mm of slump flow and J-ring were obtained, respectively. Additionally, the V-funnel time was 9.58 seconds. The use of RHA positively increased the values of the measured tests with respect to the standard, thereby improving the workability and stability properties.